2019
DOI: 10.1111/bjd.17313
|View full text |Cite
|
Sign up to set email alerts
|

Normal human skin is superior to monkey oesophagus substrate for detection of circulating BP 180‐ NC 16A‐specific IgG antibodies in bullous pemphigoid

Abstract: Summary Background Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering skin disease. Two antigens have been identified as targets of circulating autoantibodies (autoAbs) – BP180 and BP230 – with BP180 being a critical transmembrane adhesion protein of basal keratinocytes of the epidermis. The noncollagenous domain 16A (NC16A) of BP180 is the immunodominant epitope in patients with BP, and anti‐BP180‐NC16A IgG antibodies (Abs) correlate to disease activity. Routine serological testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast, direct immunofluorescence studies of lichenoid lesions may show typical features of LP: irregular band of fibrinogen at the dermal-epidermal junction and colloid bodies in the papillary dermis (53). Circulating autoantibodies in patient sera that bind to the NC16A or C-terminal domains of COL17 or desmogleins may be detected using routine methods including indirect immunofluorescence on monkey esophagus or human neonatal foreskin (54), ELISA and immunoblotting of human keratinocyte extracts (32, 55). In addition to this, circulating autoantibodies will bind to the roof of the artificial blister in indirect immunofluorescence on 1M NaCl-salt split skin (56).…”
Section: Clinical Features and Establishment Of Diagnosismentioning
confidence: 99%
“…In contrast, direct immunofluorescence studies of lichenoid lesions may show typical features of LP: irregular band of fibrinogen at the dermal-epidermal junction and colloid bodies in the papillary dermis (53). Circulating autoantibodies in patient sera that bind to the NC16A or C-terminal domains of COL17 or desmogleins may be detected using routine methods including indirect immunofluorescence on monkey esophagus or human neonatal foreskin (54), ELISA and immunoblotting of human keratinocyte extracts (32, 55). In addition to this, circulating autoantibodies will bind to the roof of the artificial blister in indirect immunofluorescence on 1M NaCl-salt split skin (56).…”
Section: Clinical Features and Establishment Of Diagnosismentioning
confidence: 99%
“…For the sensitive detection of COL17-NC16A-specific IgG, Emtenani et al reported that normal human skin was superior to monkey esophagus. The monkey esophagus was able to detect only 17% (2/12) of COL17-NC16A antibodies, whereas skin detected 100% (12/12) of the antibodies (50). Together with the low homology of COL17-NC16A between human and monkey esophagus, these pieces of evidence suggest that the expression of COL17 protein differs by anatomical location, such as skin vs. mucosa.…”
Section: Issues In Diagnosing Mmpmentioning
confidence: 98%
“…Pre-adsorption of test sera with soluble A/B blood group antigens, as a blocking step, may reduce this non-specificity [50]. Secondly, monkey oesophagus expresses very low levels of BP180 protein, the most common antigen targeted in bullous pemphigoid and, therefore, false negative diagnosis of this disease is possible if monkey oesophagus is the sole substrate used in IIF analysis [51].…”
Section: Indirect Immunofluorescence (Iif)mentioning
confidence: 99%